An Empirical Analysis of Sustainability Disclosure Practices: Evidence from India and China. (July 2014) - Bhatia, Aparna; Tuli, Siya
The present study seeks to access and compare the sustainability reporting practices in two major economies, that is, India and China. Index developed under global reporting initiative (GRI) guidelines is used. Content analysis is employed as a data collection tool. A total of 17 companies from BSE-30 (India) and 19 companies from SSE 50 (China), producing sustainability reports within the time period 2006–2007 to 2010–2011, comprise the sample set. Independent sample t test is used to compare the disclosure practices of India and China. Also, Kruskal–Wallis H test is applied for inter-category and inter-industry comparison of both countries. The results reveal that the sustainability disclosure scores are higher with respect to Indian companies as compared to Chinese companies. The results of independent sample t test are also significant at 1 per cent level of significance. However, Kruskal–Wallis H test suggests insignificant differences in the category-wise and industry-wise disclosure scores of both countries, that is, India and China. It is strongly recommended that China should strive more for sustainability practices in order to keep pace with its counterpart, that is, India.